Politeness Strategies Portrayed in Peaky Blinders Series - Muhammad Al Syidad Alamsyah Putra (Institute of Research and Community Outreach - Petra Christian University, 2025)
This qualitative study aims to find the correlation between politeness strategies and status scale when Thomas Shelby communicates to Billy Kimber, a high-status person, and to Chester Campbell, an equal-status person, in a negotiation situation by using Brown and Levinson’s (1987) politeness strategy theory and Holmes’ (2013) social dimensions theory. The source of data is the Peaky Blinders series, season 1 episode 2, and the data are Thomas Shelby’s utterances that contain politeness strategies to Billy Kimber and to Chester Campbell. The findings show that Thomas Shelby often uses negative politeness to Billy Kimber and does not use it at all to Chester Campbell. In addition, Thomas Shelby often uses one of the bald on record types to Chester Campbell compared to Billy Kimber. This study concludes that Thomas Shelby does not carelessly use politeness strategies when negotiating. Instead, Thomas Shelby considers his interlocutor's social status to choose the proper politeness strategies when negotiating. As for the future studies, the writer suggests other researchers to examine scenes other than negotiations or to identify other subjects in this series.